Solaris 10 system administration essentials (Sun Microsystems Press, 2010)
Solaris™ 10 System Administration Essentials is the first book to concisely yet comprehensively cover all of the breakthrough features of the Solaris 10 operating system. The Solaris OS has a long history of innovation, and the Solaris 10 OS is a watershed release that includes features such as Zones, which provide application isolation and facilitate server consolidation ZFS™, the file system that provides a new approach to managing your data with an easy administration interface The Fault Management Architecture, which automates fault detection and resolution The Service Management Facility, a unified model for services and service management on every Solaris system Dynamic Tracing (DTrace), for troubleshooting OS and application problems on production systems in real time In addition, the Solaris 10 OS fully supports 32-bit and 64-bit x86 platforms, as well as the SPARC ® architecture. The book's key topics include Installing, booting, and shutting down a system Managing packages and patches (software updates) Controlling system processes Managing disks and devices Managing users Configuring networks Using printing services Solaris™ 10 System Administration Essentials is part of a new series on Solaris system administration. It is a practical guide to deploying and managing the Solaris 10 operating system in a business or academic environment. The book is easy to read and rich with examples-a perfect companion for system administrators who are deploying the Solaris OS for the first time.
Print version record
Keywords: Solaris (Computer file); Electronic data processing -- Management; Systems software; Logiciels de base; Electronic data processing; Management